THE ROLE OF ADAPTIVE MILLENNIAL LEADERSHIP, ORGANIZATIONAL CULTURE, AND COMPETENCY AS A STRATEGY TO INCREASE EMPLOYEE PERFORMANCE - Dewi, Puspa; Fitrio, Tomy (Jurnal Aplikasi Manajemen, 2022)
This study aimed to develop a conceptual model of the relationship between organizational culture, competency, adaptive millennial leadership, and employee performance. Data were collected from 130 employees of Bank X of Riau Regional Office. Data were processed using Structural Equation Modeling (SEM) PLS. This study proposed adaptive millennial leadership as a strategy to improve employee performance. The results show that organizational culture and competencies mediated by adaptive millennial leadership increased employee performance. It supports the hypothesis regarding the importance of adaptive millennial leadership in improving employee performance. Also, the results strengthen social capital theory, where social capital argues that social relations are resources that can lead to the development and accumulation of human capital in achieving organizational goals.